Effect of Spacing and Plant Density on the Growth of Poplar (Populus deltoides Bartr. Ex Marsh) - Misra, K. K.; Rai, P. N.; Jaiswal, H. R. (Indian Forester, 1996)
Poplar CI. D-61 was planted at various spacing with various densities in mixed cropping system under Tarai conditions of Uttar Pradesh. Plant spacing 5 × 5 m (400 tree ha-1) and 5 × 3.75 m (533 trees ha-1 ) gave higher tree height, d.b.h, mean annual increment in d.b.h. and basal area of individual trees in comparison to other treatments after six and half years of planting. The tree survival was found significantly higher at 5 × 5 m spacing. The total volume of wood under bark was found higher at 5 × 1.25 m (1600 trees ha-1) and 5 × 1 m (200 trees ha-1) spacings.